2020
DOI: 10.3390/su13010124
|View full text |Cite
|
Sign up to set email alerts
|

Compost Inoculated with Fungi from a Mangrove Habitat Improved the Growth and Disease Defense of Vegetable Plants

Abstract: Municipal organic wastes could be exploited as fertilizers, having been given the ability to suppress plant diseases by the inoculation of the waste with certain fungi in the composting process. Our aim was to develop a novel fertilizer using composting in combination with fungi associated with mangrove forests. Nine fungal species were isolated from a mangrove forest habitat and screened for their activity against five phytopathogenic fungi, their plant-growth promotion ability, and their phosphate solubiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Species of the genera Penicillium, Aspergillus, and Talaromyces have been isolated from various substrates, including dust, soil, dung, cloth, human tissue, plants, and insects [4,11]. Due to the special ecological habitat, the fungi of these groups within tidal flats have high biodiversity and are an important source of active natural products [77][78][79][80]. Recently, three novel taxa of Penicillium were reported in tidal flats [28].…”
Section: Discussionmentioning
confidence: 99%
“…Species of the genera Penicillium, Aspergillus, and Talaromyces have been isolated from various substrates, including dust, soil, dung, cloth, human tissue, plants, and insects [4,11]. Due to the special ecological habitat, the fungi of these groups within tidal flats have high biodiversity and are an important source of active natural products [77][78][79][80]. Recently, three novel taxa of Penicillium were reported in tidal flats [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove leaf extracts inhibit the growth of human pathogens such as Staphylococcus and Salmonella (Sahoo et al, 2012). Another study inoculated compost with fungi isolated from mangrove sediments and found that plants grown in the fungal mangrove soil had higher disease defenses than plants without the fungi (Ameen and Ali, 2021). Mangroves have also been referred to as "natural wastewater wetlands" (Wu et al, 2008) and considered as secondary wastewater treatment systems in China due to their filtration capabilities (Palacios et al, 2021) Mangrove roots, may reduce viral pathogens as they are efficient desalinators, removing up to 90% of sodium ions from seawater (Kim et al, 2016).…”
Section: Mangrovesmentioning
confidence: 99%
“…Liu et al, 2018;Stapel et al, 1996;Sulawesi et al, 2001;Van Tussenbroek et al, 2017) Coral (D'Angelo & Wiedenmann, 2014) Other (macroalgae, bacterial communities, etc) (Djakouré et al, 2017;S. Liu et al, 2018) Chemical pollution Mangrove (Analuddin et al, 2017;Arumugam et al, 2018;Bhattacharya et al, 2003;Chai et al, 2019;Dudani et al, 2017;Duke et al, 2005;Ngole-Jeme et al, 2016;Proffitt et al, 1995;Qiu et al, 2019;Santos et al, 2019;Shete et al, 2009;Shi et al, 2019;Teas et al, 1987) Seagrass (Fonseca et al, 2017;Yadav et al, 2021) Microbial pollution Mangrove (Amee...…”
Section: Carbon Stocks and Nutrientsmentioning
confidence: 99%
“…The increased abundance of microbial pathogens in tropical coasts, often associated with eutrophication (section 2.4.1), could lead to a higher occurrence of infectious diseases in seagrass meadows (Hughes et al, 2018) and associated species (S. Liu et al, 2018). Furthermore, mangrove sediments have been proven to remove antibiotic-resistant bacteria from sewage effluents (H. Zhao et al, 2019), and compost inoculated with mangrove-associated fungi reduces plant disease incidence (Ameen & Al-Homaidan, 2021).…”
Section: Microbial Pollutionmentioning
confidence: 99%
See 1 more Smart Citation